Village Government Strategy in Improving Village Development in the Era of Village Autonomy: Implementation Study on Village Law in Mahakam Regency - Sirius Metodius Salang; Sapto Pramono; Sri Roekminiati; Kristyan Dwijosusilo (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
The purpose of the research is to describe and analyze the Village Government Strategy in Improving Village Development in the Era of Village Autonomy, what obstacles are experienced, and the efforts made by the Government in Improving Development in Mahakam Regency. This research is a qualitative research with a level of descriptive analysis, with data collection techniques using interviews, observations, and documentation. The data analysis technique in this study uses Miles and Huberman interactive data analysis techniques. The results of the study show that the Village Government Strategy in Efforts to Improve Village Development in Mahakam Regency is carried out with several steps, including development planning is carried out based on the musaywarah of the village development plan based on data from the lowest scope, namely the RT/RW environment based on Musrenbamg then outlined in the Village Development Work Plan. The implementation of development is carried out based on the Development Budget Plan, namely what priorities will be implemented, which are managed on a local scale through village self-management, village cooperation with third parties. The process of monitoring and evaluating development is carried out at the village and sub-district levels assisted by community institutions that check the list of activities listed in the Development Work Plan document stipulated in the Village Budget. The development supervision process is carried out through community institutions and community leaders. Obstacles in the development of villages in Mahakam Regency include, among others, the desired development has not been achieved, this is due to the difficulty of obtaining a budget. Efforts made include proposing a village Musrenbang next year, making a medium-term long-term development plan for a term of 5 years and including RKA and RKP.